Effect of sodium phenylbutyrate/taurursodiol on tracheostomy/ventilation-free survival and hospitalisation in amyotrophic lateral sclerosis: long-term results from the CENTAUR trial. Issue 8 (16th May 2022) - Paganoni, Sabrina; Hendrix, Suzanne; Dickson, Samuel P; Knowlton, Newman; Berry, James D; Elliott, Michael A; Maiser, Samuel; Karam, Chafic; Caress, James B; Owegi, Margaret Ayo; Quick, Adam; Wymer, James; et al.
Abstract : Background: Coformulated sodium phenylbutyrate/taurursodiol (PB/TURSO) was shown to prolong survival and slow functional decline in amyotrophic lateral sclerosis (ALS). Objective: Determine whether PB/TURSO prolonged tracheostomy/ventilation-free survival and/or reduced first hospitalisation in participants with ALS in the CENTAUR trial. Methods: Adults with El Escorial Definite ALS ≤18 months from symptom onset were randomised to PB/ TURSO or placebo for 6 months. Those completing randomised treatment could enrol in an open-label extension (OLE) phase and receive PB/TURSO for ≤30 months. Times to the following individual or combined key events were compared in the originally randomised treatment groups over a period spanning trial start through July 2020 (longest postrandomisation follow-up, 35 months): death, tracheostomy, permanent assisted ventilation (PAV) and first hospitalisation. Results: Risk of any key event was 47% lower in those originally randomised to PB/TURSO (n=87) versus placebo (n=48, 71% of whom received delayed-start PB/TURSO in the OLE phase) (HR=0.53; 95% CI 0.35 to 0.81; p=0.003). Risks of death or tracheostomy/PAV (HR=0.51; 95% CI 0.32 to 0.84; p=0.007) and first hospitalisation (HR=0.56; 95% CI 0.34 to 0.95; p=0.03) were also decreased in those originally randomised to PB/TURSO. Conclusions: Early PB/TURSO prolonged tracheostomy/PAV-free survival and delayed first hospitalisation in ALS. Trial registration number: NCT03127514 ; NCT03488524 .